Moderators and mediators of the relationship between parental depression and children’s emotion dysregulation: a systematic review - Sabalbal, Ahmad; El Hayek, Samer; Baroud, Evelyne; Shamseddeen, Wael (Frontiers in Psychiatry, 2025)
BackgroundParental depression is an important risk factor for the development of psychopathology in children/adolescents. Many children who suffer from psychopathology also experience emotion dysregulation, which is characterized by an inability to modulate the intensity and quality of emotions. Emotion dysregulation carries high morbidity and predicts ongoing mood/behavior problems. To develop more effective intervention and prevention programs, it is important to understand the variables that mediate and moderate the relationship between parental depression and children’s emotion dysregulation. This study aimed to systematically explore possible mediators and moderators.MethodsThe PubMed, Scopus, PsycINFO, and Embase databases were systematically searched from day of inception until January 12, 2024. The reference lists of the reviews of interest identified during the screening were included. Two authors screened/collected articles through title and abstract screening, followed by full-text screening. The results were qualitatively synthesized. The inclusion criteria were: population, children/adolescents (aged 0–17 years); exposure, parental depression; outcome, emotion dysregulation; and study design, quantitative.ResultsA total of 1,731 studies were identified, of which 556 were potentially eligible. After removing duplicates/retracted articles, 380 records were screened (title/abstract), following which 315 records were excluded. Of the remaining 65 studies, eight met the inclusion criteria after full-text screening. Most of the studies (n = 6) included mothers. Biological variables and variables related to the child, to parental depression severity, and to child–parent interactions emerged. The biological variables (the child’s genotype and left parietal alpha asymmetry) highlight a biological vulnerability to dysregulation beyond parent–child effects and environmental factors: left parietal alpha asymmetry was a partial mediator, while genotype was a moderator as children carriers of the S/LG genotypes experienced higher levels of dysregulation as a function of exposure to higher levels of prenatal maternal depression. Depression severity and parent–child dyadic variability were moderators as elevated levels of dysregulation among girls were predicted by greater maternal depression severity and mothers who were more inconsistent in parenting behaviors were more likely to have toddlers with dysregulation, especially if the mothers were depressed. Diet was a mediator, and more severely depressed mothers were more likely to feed their children unhealthy diets, in turn leading to greater dysregulation in later years. Parenting stress mediated the relationship between maternal depression and dysregulation in toddlers.ConclusionsChildren of depressed parents are a vulnerable group and are prone to developing emotion dysregulation. The findings suggest that prevention/intervention programs should target the children of more severely depressed parents and those of parents who engage in more negative interactions with them. Children’s diet and parenting stress are also potential evidence-based, modifiable intervention targets.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024502390.